2023
DOI: 10.1182/bloodadvances.2022009067
|View full text |Cite
|
Sign up to set email alerts
|

Vemurafenib combined with cladribine and cytarabine results in durable remission of pediatric BRAF V600E–positive LCH

Dmitry Evseev,
Daria Osipova,
Irina Kalinina
et al.

Abstract: Langerhans cell histiocytosis (LCH) is a disorder with a variety of clinical signs. The most severe forms affect "risk organs" (RO). The established role of BRAF V600E mutation in LCH led to a targeted approach. However, the targeted therapy can't cure the disease and the cessation leads to quick relapses. In our study, we combined cytarabine (Ara-C) and 2'-chlorodeoxyadenosine (2-CdA) with targeted therapy to achieve stable remission. Nineteen children were enrolled in the study: 13 RO+ and 6 RO-. Five patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…One patient developed secondary myelodysplastic syndrome, but other toxicities were reportedly manageable. 19 The patients in our study were similar at the age of diagnosis (1.15 years vs. 10 months for RO+ and 24 months for RO−), but older and with longer treatment history compared to the Evseev series (6.8 years vs. 17 months for RO+ and 24 months for RO−; median 4 prior therapies vs. 2). In this study, ORR was comparable (90% vs. 100%) in a challenging population treated with less toxic therapy that can be administered outpatient in most cases.…”
Section: Optimizing Outcomes For Lch Patientsmentioning
confidence: 55%
“…One patient developed secondary myelodysplastic syndrome, but other toxicities were reportedly manageable. 19 The patients in our study were similar at the age of diagnosis (1.15 years vs. 10 months for RO+ and 24 months for RO−), but older and with longer treatment history compared to the Evseev series (6.8 years vs. 17 months for RO+ and 24 months for RO−; median 4 prior therapies vs. 2). In this study, ORR was comparable (90% vs. 100%) in a challenging population treated with less toxic therapy that can be administered outpatient in most cases.…”
Section: Optimizing Outcomes For Lch Patientsmentioning
confidence: 55%
“…Evseev, D found that combined cytarabine (Ara-C) and 2'-chlorodeoxyadenosine (2-CdA) with vemurafenib achieved stable remission in LCH patients, but all patients experienced grade 3–4 hematological adverse reactions. One patient developed secondary myelodysplastic syndrome (sMDS) 14 months after vemurafenib therapy cessation (Evseev et al 2023 ). In our study, we administered vemurafenib in combination with low-toxicity chemotherapy for over 12 months to the majority of patients, and most of them achieved clinical and molecular remission.…”
Section: Discussionmentioning
confidence: 99%
“…COMMENTARY combination cladribine, cytarabine and vemurafenib in patients with BRAFV600E-positive LCH, achieving a 2-year event-free survival rate of 78.9%. 8 The vemurafenib was administered sequentially to avoid the risk of overlapping toxicities. Notably, none of the participants had previously received MAPK inhibition, and only one had been treated with cladribine.…”
mentioning
confidence: 99%
“…Recently, Evseev et al. presented findings from a prospective phase II trial that investigated the efficacy of combination cladribine, cytarabine and vemurafenib in patients with BRAFV600E‐positive LCH, achieving a 2‐year event‐free survival rate of 78.9% 8 . The vemurafenib was administered sequentially to avoid the risk of overlapping toxicities.…”
mentioning
confidence: 99%